Biohealth tracking: sistema baseado em tecnologias de controle por gesto aplicado para saúde e esporte - Vendramini, Marcos Dias (2017)
The advent of new technologies has contributed to advances in motion capture and its physical exercise application. The use of motion capture technology is attractive due to its low cost of hardware acquisition. Conventional treatments in physiotherapy are, for the most part, longlasting and repetitive, which makes the patient see it as tiring and discouraging, a perception that interferes with therapeutic efficacy. With regard to weight lifting, young athletes have injuries that may leave them out of competitions, and some of these injuries may occur due to lack of basic principles of weight training. A monitoring system can provide better patient/athlete control during the treatment or training session through continuous monitoring. This dissertation presents software for the area of physiotherapy and Olympic weightlifting, aiming to assist the physiotherapist/coach in monitoring the exercises performed by the patients/athletes. BHTracking - BioHealth Tracking is available, including its source code, under the GNU General Public License (GPL). The software was implemented with gesture control technologies, mapping the patient/athlete’s body and tracking the exercise during its execution. The basis of its functioning is in the system of validation of the exercise by comparison of angles and references of the body points, with models of correct movements previously stored. The software also provides feedback on the evolution of the patient or athlete analyzed, comparing the movements of the same exercise throughout the treatment/training.